Diversity of insect pest in oil palm nursery at Kesedar Dagang Sdn Bhd, Gua Musang, Kelantan / Nur Azwa Nafesha Mat Amin - Mat Amin, Nur Azwa Nafesha (Faculty of Plantation and Agrotechnology, 2016)
A study on diversity of insect pest in oil palm nursery that was carried out at Kesedar Dagang Sdn Bhd, Gua Musang, Kelantan from January to February 2016. The study aims to recognized types of insect and discovered the major and minor insect group favour in that field. Both of yellow pan and yellow sticky trap were used to lure insect approach the field. The yellow pan contains soapy water were placed on the ground level and yellow sticky trap was set up on the height above plant level. Ladybug (Menochilus sexmaculatus), Green fly (Lucilia sericata), Fruit fly (Bactrocera dorsalis) and True bug (Dysdercus cingulatus) are the common insect found in this oil palm nursery. The normality had shown that the data of these insect were not normally distributed. Hence, Kruskal wallis was tested to identify significant different among different time of collection. It showed that all these insect were not significant except true bug among different time of collection.The result from T- test shown that LB (F = 56.951; df= 78; p<O.OO) and TB (F = 46.803; df= 78; p<0.05) were significant while GF (F = 2.674; df = 78; p> 1.00) and FF (F = 6.042; df = 78; p> 2.62) were not significant among different time of collection. This study also found that True bug has the largest population with 31% compared with another three insect while Fruit fly is the lowest population with only 17% found in this field.